Effects of Transport Temperature on the Stability of Inflammatory, Hemostasis, Endothelial Function, and Oxidative Stress Plasma Biomarker Concentrations. Issue 6 (June 2017) - Palmer, Octavia M. Peck; Carter, Melinda; Chang, Chung-Chou H.; Lucko, Nicole; Jackson, Vanessa M.; Sun, Qian; Xie, Xinyan; Scott, Melanie; Kellum, John A.; Venkat, Arvind; Yende, Sachin
ABSTRACT: Background: A number of studies in critically ill patients are conducted outside the hospital. Specimens should ideally be transported from out-of-hospital setting to a laboratory using dry ice, but this approach is expensive and may not be feasible in some circumstances. We, therefore, examined the impact of temperature during transport of specimens on the precision of biomarker concentrations. Objective: To determine the effects of transport temperature conditions on biomarker concentrations in specimens processed within 1 h of collection. Methods/Patients: We simulated transport by storing specimens at four temperature conditions: packaged at −80°C (control), on dry ice (−79°C), on cold gel packs (4°C), and at room temperature (RT, 21°C). We examined eight biomarkers spanning four signaling domains— inflammation, hemostasis, endothelial dysfunction, and oxidative stress. We calculated mean, median, and percent difference for each biomarker concentration compared with the control transport temperature at −80°C in 26 subjects (16 hospitalized with severe sepsis and 10 non-hospitalized volunteers). Results: Patients with severe sepsis had log-fold higher median concentrations of IL-6, hs-CRP, D-dimer, E-selectin, sICAM-1, and sVCAM-1 compared with non-hospitalized volunteers ( P <0.05). When specimens were combined, we observed a ⩽7% difference in the mean and median IL-6, hs-CRP, D-dimer, PAI-1, E-selectin, s-ICAM, s-VCAM, and nitrite concentrations for dry ice and cold gel packs transport compared with transport at −80°C ( P >0.05). Larger differences (up to 12%) were observed when biomarker concentrations for PAI-1 and s-VCAM at room temperature were compared with transport at −80°C ( P >0.05). Conclusions: Select inflammatory, coagulation, endothelial dysfunction, and oxidative stress biomarkers can be transported at 4°C on gel packs for 24 h with minimal effects on precision. Abstract : Supplemental Digital Content is available in the text